Pyrethroid resistance in Aedes aegypti and Aedes albopictus: Important mosquito vectors of human diseases - Smith, Letícia B.; Kasai, Shinji; Scott, Jeffrey G. (Pesticide biochemistry and physiology, 2016)
Aedes aegypti and A. albopictus mosquitoes are vectors of important human disease viruses, including dengue, yellow fever, chikungunya and Zika. Pyrethroid insecticides are widely used to control adult Aedes mosquitoes, especially during disease outbreaks. Herein, we review the status of pyrethroid resistance in A. aegypti and A. albopictus, mechanisms of resistance, fitness costs associated with resistance alleles and provide suggestions for future research. The widespread use of pyrethroids has given rise to many populations with varying levels of resistance worldwide, albeit with substantial geographical variation. In adult A. aegypti and A. albopictus, resistance levels are generally lower in Asia, Africa and the USA, and higher in Latin America, although there are exceptions. Susceptible populations still exist in several areas of the world, particularly in Asia and South America. Resistance to pyrethroids in larvae is also geographically widespread. The two major mechanisms of pyrethroid resistance are increased detoxification due to P450-monooxygenases, and mutations in the voltage sensitive sodium channel (Vssc) gene. Several P450s have been putatively associated with insecticide resistance, but the specific P450s involved are not fully elucidated. Pyrethroid resistance can be due to single mutations or combinations of mutations in Vssc. The presence of multiple Vssc mutations can lead to extremely high levels of resistance. Suggestions for future research needs are presented. [Display omitted] •Pyrethroid insecticides continue to be the primary means for control of adult Aedes.•Resistance to pyrethroids has been found throughout the world, but levels vary.•Resistance is primarily due to mutations in Vssc and P450-mediated detoxification.•Multiple Vssc mutations can result in highly resistant populations.•Numerous areas will require more study in order to slow the evolution of resistance.